VD_FINDINFO Jug / 2020 / 458 vom 26. Februar 2020 - VD Tribunal cantonal (2020)
REPRÉSENTATION DE LA VIOLENCE, CONTRAINTE SEXUELLE, PORNOGRAPHIE, TENTATIVE SIMPLE | 135 CP, 189 al. 1 CP, 22 ad 189 al. 1 CP, 66a al. 2 CP